The aesthetics of poetic discourse in the collection (He Who Comes to My States) by the poet Abdul Wahhab Al-Bayati (Journal of the College of Basic Education, 2025)
The following research delves into a literary-aesthetic treatment of poetic discourse in Al-Bayati’s collection “He Who Comes and Does Not Come,” attempting to grasp the aesthetics of the discourse and the interpretations achieved by the poetic nature of the text. Like his peers, Al-Bayati tended toward an experimental tendency, moving toward modernism and working with its mechanisms.The study in hand attempts to trace the transformations that accompanied the creative experience of poetic discourse in Al-Bayati’s work—transformations imposed by the effects of modernism that emerged in thought and artistic taste, which became open to foreign culture and the accompanying transformations in poetic text. These changes pushed poetry to break away from the familiar, represented by the unified rhyme, which had become a burden on poets who wanted to express their contemporary issues—toward an openness to adventures that made poetry and prose sail in the same boat . In addition, it addresses the poetic discourse’s aesthetics of poetic in Al-Bayati’s collection “He Who Comes and Does Not Come.” This, in turn, represents an aesthetic harmony between word and meaning, and highlights the new expressive transformations that accompanied his texts, in which the poem performed the act of breaking away from the poetic model by imposing new laws of creativity in both form and content.The research in hand also addresses the nature of the discourse, its mechanisms, artistic features, and aesthetic dimensions. The research discusses the school to which Al-Bayati belongs, which formed a prominent influence on his poetry.The researcher had adopted a research plan beginning with an introduction, followed by a brief biography of Al-Bayati and some background on the collection “He Who Comes and Does Not Come.” The first chapter explains the conceptual and terminological framework as a theoretical aspect, leading to the second chapter, which is an applied study of the collection. This study is based on the fourth edition, published in 1985 by Dar Al-Shorouk, Cairo.